Actual Evapotranspiration Comparison in Hanjiang River and Weihe River Basin Based on Multiple Methods - LI Tongtong; LIU Dengfeng; MING Guanghui; HAN Songjun; MENG Xianmeng; HUANG Qiang (Renmin Zhujiang)
Accurate actual evapotranspiration assessment in a basin is important for revealing climate change trends and serving regional water resources management.The Hanjiang River and Weihe River are typical representatives of semi-humid and semi-arid watersheds on the north and south sides of the Qinling Mountains.This paper estimates and verifies the mean annual actual evapotranspiration of basins in the Hanjiang River and Weihe River basins by multiple methods including the water balance method, B2015 evapotranspiration complementary model, SWAT hydrological model, and evapotranspiration data products.The results show that the B2015 evapotranspiration complementary model is well applied to both study areas, and the calculated actual evapotranspiration error is less than 10%.The SWAT model performs well in the daily runoff simulation in both study areas, and the determination coefficient is larger than 0.63.The comparison results of multiple methods show that the annual actual evapotranspiration calculated by the water balance method and the SWAT model is closer to the actual value, and the calculated values of the B2015 evapotranspiration complementary model in Hanjiang River and Weihe River are 3.79% and 2.46% smaller than the actual values respectively.The actual evapotranspiration from the TEDAC and GLDAS evapotranspiration products is 31.08% and 36.54% larger in Hanjiang River and 13.72% and 5.06% larger in Weihe River, and the evaluation performance of the two products is better in the Weihe River than that in Hanjiang River.Additionally, it is still difficult to calculate the accurate actual evapotranspiration by current datasets and methods in specific basins.